Pengaruh Pembelajaran Kooperatif dan Gaya Belajar Terhadap Keterampilan Menulis Bahasa Jerman Mahasiswa - Harianto, Harianto; Dalle, Ambo; Anwar, Muh. (Universitas Negeri Makassar, 2021)
Abstract. The study is a quasi experiment using the two-way ANAVA test which aims to obtain data on the influence of cooperative learning and learning styles on German writing skills. The experimental method used was a 2x2 factorial design. The sample of the study was 20 students of German Education Study Program batch 2019 of Class A. The results of this study reveal that (1) the results of the two-way ANAVA test obtained the value of fcount (0.049) < ftabel (4.45) at the significant level Î± = 0, 05, so there is an influence of cooperative learning on German writing skills of students of German Language Education Study Program at FBS UNM, (2) the results of the two-way ANAVA test obtained the value of fcount (0.049) < ftable (4.45) at a significant level of Î± = 0.05, so there is an influence of learning style on German writing skills of students of German Language Education Study Program at FBS UNM, and (3) the results of the two-way ANAVA test obtained the value of interaction fcount (I) = 3.95 < ftabel = 4.45 at the significant level Î± = 0.05. Therefore, the conclusion of the study is there is an interaction between cooperative learning and learning styles on German writing skills of students of German Language Education Study Program at FBS UNM